Teachers’ Perceived Impact of an Online Professional Development Course on Content and Language Integration and Pedagogical Translanguaging - Fazzi, Fabiana (International Journal of Linguistics, 2022)
Research has already shown that designing instruction that simultaneously develops students’ content and language competences is fundamental especially, but not only, when students are educated in a second, foreign or additional language. Unfortunately, content teachers working in different types of bilingual education programmes hold varying beliefs about the role of language for and in learning and often struggle to successfully integrate language and content objectives. This is particularly the case of content teachers working in the Italian network of educational institutions in the world who struggle to support students to learn content through Italian as the language of instruction, but also tend to fail to recognize the importance of validating their linguistic and cultural background. In this context, the dearth of training is accompanied by a dearth of research on the effects of professional development courses. This paper aims to fill this gap by reporting on the effectiveness of a short online teacher professional development (OTPD) course aimed at supporting both primary and secondary subject teachers working in Italian international schools abroad to integrate content and language learning from a plurilingual and pluricultural perspective. Specifically, it explores teachers’ perceptions in relation to the design and implementation features of the course and to its effects on their beliefs, teaching practice, and professional identity.